Resolving the origin of very-high-energy gamma-ray emission from the PeVatron candidate SNR G106.3+2.7 using MAGIC telescopes - Oka T.; Saito T.; Kubo H.; Strzys M.; Acciari V.A.; Ansoldi S.; Antonelli L.A.; Arbet Engels A.; Artero M.; Asano K.; Baack D.; Babić A.; et al. (Italy, 2025)
The supernova remnant (SNR) G106.3+2.7 associated with a 100 TeV gamma-ray source reported by HAWC, Tibet ASγ, and LHAASO Collaborations is one of the promising PeVatron candidates. Because the SNR contains an energetic pulsar wind nebula (PWN) dubbed Boomerang powered by the pulsar PSR J2229+6114, it is unclear whether the gamma-ray emission originates from the SNR or PWN complex and whether it is caused by hadronic or leptonic processes. We observed gamma rays above 200 GeV in the vicinity of the SNR G106.3+2.7 using the MAGIC telescopes for total ∼ 120 hours between May 2017 and August 2019 with an angular resolution of 0.07-0.10 degrees, achieving an unprecedented exposure for this object at these energies. An extended gamma-ray emission spatially correlated with the radio continuum emission at the head and tail of SNR G106.3+2.7 was detected using the MAGIC telescopes. We found a significant gamma-ray emission above 5.65 TeV only from the SNR tail region, while no significant emission in the same band is found at the SNR head region containing the Boomerang PWN. Therefore, the gamma rays above 10 TeV detected with the air shower experiments are, likely, mainly emitted from the SNR tail region. In this presentation, we discuss the morphology of the gamma-ray emission from this complex region and attempt self-consistent multi-wavelength modeling of the energy spectrum.
37th International Cosmic Ray Conference (ICRC2021)